2009
DOI: 10.1007/s12575-009-9017-9
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Monitoring of Cellular Remodeling Induced by the Transforming Growth Factor-β1

Abstract: The plasticity of differentiated adult cells could have a great therapeutic potential, but at the same time, it is characteristic of progression of serious pathological states such as cancer and fibrosis. In this study, we report on the application of a real-time noninvasive system for dynamic monitoring of cellular plasticity. Analysis of the cell impedance profile recorded as cell index using a real-time cell analyzer revealed its significant increase after the treatment of prostate epithelial cells with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 10 publications
3
19
0
Order By: Relevance
“…These observations are in agreement with a previously published study by Jacksch et al demonstrating the higher colony-forming capacity of CD133 high Caco2 colon cancer cells (22). Label-free RTCA based on the detection of cellular impedance had great potential in both basic and applied research (16,17,23,24). In this study, we revealed for the first time that it is possible to combine the direct deposition of a limited number of immunolabeled cells with long-term, real-time, label-free analysis of cell proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…These observations are in agreement with a previously published study by Jacksch et al demonstrating the higher colony-forming capacity of CD133 high Caco2 colon cancer cells (22). Label-free RTCA based on the detection of cellular impedance had great potential in both basic and applied research (16,17,23,24). In this study, we revealed for the first time that it is possible to combine the direct deposition of a limited number of immunolabeled cells with long-term, real-time, label-free analysis of cell proliferation.…”
Section: Discussionsupporting
confidence: 91%
“…12,13 Such hypothesis was confirmed in Figure 6e as we could observe an induction of Figure S4d). 43 Altogether, these data clearly suggest that the absence of TAp73 impairs TGF-β signaling toward the tumor suppressing SMAD4-dependent pathway.…”
Section: Resultsmentioning
confidence: 81%
“…Growth factor-induced morphological changes can be quantified in cells by measuring impedance (36,37), which provides a real-time, noninvasive analysis suitable for measuring the kinetics of short-and long-term cellular responses. Changes in cellular impedance triggered by agents such as EGF and insulin have been shown to correlate with those measured by conventional means [e.g., autophosphorylation of the EGF receptor as measured by ELISA (36)], and impedance now is commonly used for assessing morphological changes such as membrane ruffling or formation of lamellipodia in a quantita- tive fashion.…”
Section: Resultsmentioning
confidence: 99%